'Hack the map', a digital educational program inspired by Rigas Velestinlis' Charta of Greece (1796–1797). Issue 1 (2nd January 2022) - Pazarli, Maria; Diamantis, Kostas; Gerontopoulou, Vasiliki
ABSTRACT: Occasioned by the celebration of the 200 years since the outbreak of the Greek Revolution of 1821, Onassis Library, in collaboration with the Cartographic Heritage Archives of General State Archives of Greece and the Department of Geography of Harokopio University, designed a series of four digital workshops to motivate teenagers to bring to life one of the most emblematic maps of the so-called Greek Enlightenment during the eighteenth century and major item of the Greek cartographic heritage: Rigas Velestinlis Charta (map) of Greece (1796–1797) . From January to March 2020, four school teams consisting of students 13–17 years old, approached in a creative way the map that inspired the Greek Revolution of 1821, transforming it into a computer game, a digital story, an augmented reality or a virtual reality application. By using innovative mixtures of history, geography, cartography, visual arts and information technology, they managed to expand their knowledge and skills by participating in an entertaining learning process. All participants acknowledged the pedagogical value of this innovative experience, which cultivated a positive attitude towards the learning procedure, enriching the lessons of history and geography, promoting the cartographic cultural heritage through new technology approaches and using valuable digital techniques and tools.